The state of postpartum contraceptive use in India: descriptive lessons from nationally representative survey data - Nicole E. Johns; Abhishek Singh; Shruti Ambast; Nandita Bhan; Katherine Hay; Vedavati Patwardhan; Lotus McDougal (Reproductive Health)
Abstract Background Postpartum contraception is a key tool to delay or prevent subsequent pregnancy after birth. Though prior research has demonstrated substantial dynamism in contraceptive use throughout the postpartum period, most measurement of postpartum contraception has focused on aggregate use of any method at a single time point. We sought to more thoroughly examine the continuum of postpartum contraceptive use amongst women in India. Methods We use 2019–21 National Family and Health Survey reproductive calendar data from n = 149,518 women with a birth in the one to five years prior to survey. We present estimates of postpartum contraceptive use by month postpartum, use of specific methods, initiation, duration, stopping, method switching, and subsequent pregnancy. We examine sociodemographic and birth factors associated with postpartum contraceptive use using multivariate logistic regression models. We also examine patterns of postpartum utilization for subpopulations of interest (adolescent mothers age 15–19 and first time mothers) and test whether conclusions are sensitive to a two-year rather than one-year postpartum time period definition. Results We find that 59% of Indian women used a method of contraception within the first year postpartum, that condoms and female sterilization were the most commonly used methods, and that patterns of postpartum contraceptive use differed substantially by month, method, and subpopulation. Among postpartum contraceptive users, 9% switched methods, 19% stopped using contraception entirely, and 5% had another pregnancy within the first year postpartum. A number of sociodemographic and birth factors are associated with postpartum contraceptive utilization, and patterns of use differ meaningfully for adolescent and first-time mothers. Most findings were consistent when using a two-year rather than one-year time frame. Conclusions The dynamic nature of postpartum contraceptive use suggests limited value of static contraceptive uptake targets, whether for program planning or as measures of success, and bolsters the need to center and to improve reproductive agency, empowerment, and access throughout the postpartum period.